South Africa’s Nuclear Programme and the Cold War - Van Wyk, Anna-Mart (History compass, 2010)
In March 1993, South African State President F. W. de Klerk stunned the world with an announcement that the South African Apartheid Government had developed six and a half nuclear bombs during a top-secret 15-year programme. A number of factors led to the decision to develop nuclear weapons; the most important being Pretoria’s fear from the mid-1970s that a communist takeover in Southern Africa was imminent and that they needed a suitable deterrent to ensure the security of South Africa and their own position of power. It was specifically the involvement of Cuba and the Soviet Union in the Angolan Civil War that led Pretoria to a formal decision in 1978 to develop a limited nuclear capability. At the end of the 1980s, however, the collapse of the Soviet Union, the withdrawal of Cuban troops from Angola, the independence of Namibia, and the imminent democratisation of South Africa brought a rapid end to the perceived ideological and security threat to South Africa and indeed made the deterrence factor of the nuclear arsenal obsolete. In August 1989, Pretoria decided to destroy the arsenal, thereby becoming the first country to voluntarily destroy a nuclear arsenal before acceding to the NPT, which happened in July 1991. This article provides a chronological overview of Apartheid South Africa’s development of a nuclear arsenal, within the framework of the Cold War.